Evaluasi Akuntabilitas Kinerja (SAKIP) Pada Instansi Pemerintah Daerah Kota Surabaya : Studi Kasus: RSUD Dr. Mohamad Soewandhie - Sefty Maharani Devi; Muhammad Roisul Basyar (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The performance accountability evaluation (SAKIP) is crucial for assessing the success and shortcomings of government institutions in fulfilling their tasks and functions. This study evaluates the SAKIP implementation in the Regional Public Hospital (RSUD) Dr. Mohamad Soewandhie in Surabaya City. Through qualitative research methods, the study examines the planning, measurement, reporting, and internal performance accountability evaluation. The findings reveal that RSUD Dr. Mohamad Soewandhie demonstrates a high level of performance accountability, scoring an overall rating of 92.20 out of 100, categorized as "very satisfactory." Factors influencing its performance accountability include internal elements such as planning quality, performance measurement, and internal evaluation, as well as external factors like government regulations, external oversight, and societal expectations. The implications suggest areas for improvement and reinforcement of the hospital's performance accountability, contributing to better healthcare service delivery and transparency.